An essay describing the design process for a community facilities building in Bokaap - Townsend, Stephen (School of Architecture, Planning and Geomatics, 2016)
Any part of the built environment reflects the relative importance, or lack of importance, of four categories of determinants as experienced by the makers of that environment. These four categories are the People, the Function, the Place and finally the Style, Aesthetic or Vernacular of the makers. The first three of these, though complexly inter-related and inter-dependant, can be analysed and understood as separate categories. The People, Client or User can be analysed in terms of demography, historical background, technological development, societal structure, culture, religion, aspirations and attitudes. The Function, or Usage involves the understanding of both the specific need of the user and also the universal or archetypal prototype of the typical user. The Place, or Site must be understood in terms of movement to/through/ around it, aspect and prospect, topography, relationships to the surroundings, climate and vegetation. Each of these three categories of given information must be analysed and fully understood by the makers of the environment. Simply to be useful the environment must satisfy these factors fully. However, the designer or maker of the environment is free to interpret these factors in any way he chooses. Whether he likes it or not, he assigns relative values and he makes arbitrary decisions of which he is not even vaguely conscious. Thus even the supposedly objective analysis of determinants is riddled with subjective evaluations. The fourth category, that of Style or Aesthetic is rather less tangible than those just mentioned, and consequently even further removed from rational decision-making process, but at the same time inextricably tied to determinants like technology, culture, use and site. Thus the designer or maker of the environment gives it expression that has very little to do with the pragmatic demands of User, Function and Site (though he often, even usually, rationalizes architectural expression in terms of the givens). This essay is a modest attempt to show the interplay of objective and subjective, rational and irrational decision making in the process leading to the design of a Community Facilities Building in Bokaap. The form that the essay will take is as follows: Each of the four categories of determinants will be treated in turn; with an objective description of subject matter concerning the category being found in a wider column on the right side of each page. In the smaller column on the left is commentary of a subjective nature on design decisions taken and various miscellaneous observations.